Hydrogeochemical and Isotopic Investigations on Groundwater Salinization in the Datong Basin, Northern China1. (28th January 2013) - Xie, Xianjun; Wang, Yanxin; Li, Junxia; Su, Chunli; Duan, Mengyu
Abstract : Abstract:  Analyses of major elements, environmental isotope ratios (δ 18 O, δ 2 H), and PHREEQC inverse modeling investigations were conducted to understand the processes controlling the salinization of groundwater within the Datong Basin. The hydrochemical results showed that groundwater with high total dissolved solid (TDS) concentrations was dominated by sodium bicarbonate (Na‐HCO3 ), sodium chlorite (Na‐Cl), and sodium sulfate (Na‐SO4 ) type waters, whereas low‐TDS groundwater from near mountain areas was dominated by calcium bicarbonate (Ca‐HCO3 ) and magnesium bicarbonate (Mg‐HCO3 ) type waters. The characterization of the major components of groundwater and PHREEQC inverse modeling indicated that the aluminosilicate hydrolysis, cation exchange, and dissolution of evaporites (halite, mirabilite, and gypsum) governed the salinization of groundwater within the Datong Basin. The environmental isotope (δ 18 O, δ 2 H) and Cl − /Br − ratios revealed the impact of fast vertical recharge by irrigation returns and salt‐flushing water on the groundwater salinization. According to the analyses of major hydrochemical components and PHREEQC inverse modeling, evaporite dissolution associated with irrigation and salt‐flushing practice was probably the dominant controlling factor for the groundwater salinization, especially in the central part of the basin. Therefore, groundwater pumping for irrigation and salt‐flushing should be controlled to protect groundwater quality in this area.